Sistem Kekerabatan dan Pengaruhnya Terhadap Hukum Waris Islam - Halimatul Maryani; Adawiyah Nasution; Dani Sintara; Bonanda Japatani Siregar (LEGAL BRIEF, 2022)
The Indonesian nation is famous for its diversity of different ethnic groups, races, ethnicities, cultures, and religions, giving rise to certain uniqueness such as regulating the character of one's personality as a family member. There are three forms of the kinship system that exist in Indonesia in terms of continuing the offspring in the family, namely unilateral, parental, and multilateral. Laws in Indonesia are also very diverse due to the influence of the conditions of the pluralistic society, including different customs. This paper will discuss only two hereditary systems. Well, the lineage system in unilateral form is an interesting system of lineages. There are two forms of this unilateral system, namely patrilineal and matrilineal. The patrilineal system is a family kinship system that is enforced by looking at the lineage of the father such as the Batak, Lampung, Gayo, and others, meaning that a person's or family's lineage system connects himself to the father, entirely upward to the father of the father as an example of "Marga". For the Batak clan, the clan is followed by the father's lineage and genealogy, from top to bottom. As for the matrilineal, this is the opposite kinship system from the father, namely the continuation system in the family is enforced by looking at the lineage of the mother, meaning that each person will always connect himself to the mother, like the Minangkabau tribe, then the family relationship is drawn upwards from maternal lineage, also downwards. The aim is to examine the influence of the existing kinship system in Indonesia on Islamic inheritance law, using a combination of normative juridical and sociological juridical methods.